Identifying the predictors of turnover intention based on nurse managers' toxic leadership behaviors among nurses in Iran: a cross-sectional correlational study - Elham Ahangari Nonehkaran; Naser Mozaffari; Sohrab Iranpour; Aghil Habibi Soola (BMC, 2023)
Abstract Background Unfavorable leadership practices are a growing concern in the field of healthcare and nursing that have adverse consequences on nurses' career outcomes. One of the undesirable leadership styles is the toxic leadership style. Considering the importance of nursing managers' leadership style and its impact on nurses' performance and the scarcity of studies in this field, the present study was conducted to determine toxic leadership behaviors in nursing managers and their relationship with the turnover intention among nurses. Methods A multicenter cross-sectional correlational study. This study involved 551 nurses from 5 educational-medical centers in Ardabil province, north-western Iran. Three self-report scales, including The demographic and occupational information form, the Toxic Leadership Behaviors of Nurse Managers Scale (ToxBH-NM), and the turnover intention questionnaire were adopted for assessment purposes in this study. Data were analyzed using SPSS (Version 22) software using descriptive statistics, Pearson correlation coefficient test, t-test, ANOVA test, and multiple linear regression analysis. Results Overall, 551 nurses participated in this research. There was a significantly positive relationship between Turnover intention and Toxic leadership behavior Subscales (r = 0.475, p < 0.001). Furthermore, multiple linear regression analysis showed Toxic leadership behavior Subscales (Intemperate behavior, Narcissistic behavior, Self-promoting behavior, and Humiliating behavior), Hospital, unit, Age, and Marital status predict Turnover intention when other variables are controlled. Conclusion A leader who directly and indirectly adopts toxic behavior toward their employees destructively affects both individuals and organizations. Nurses who work for a manager exhibiting toxic leadership behaviors demonstrated higher turnover intention.